2012
DOI: 10.1603/ec11202
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Method for Separation of House Fly (Diptera: Muscidae) Larvae From Processed Pig Manure

Abstract: A behavioral method applicable in biodegradation facilities for separation of house fly (Musca domestica L.) larvae from processed pig manure is presented. The method is based on placing a cover over the larval rearing tray, while escaping larvae are collected in collection trays. Separation units must be placed in a dark room to avoid negative phototactic responses of the larvae. After 24 h of separation, over 70% of the larvae escaped from processed manure and were collected in collection trays. Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…D) [4]. During the past decade, due to the antibacterial activity of housefly larvae and its products, they have been used mainly in preservation [11], environmental protection [12], and inhibition of multiresistant bacteria [13]. In recent years, several reports suggested that atherosclerosis is a chronic inflammatory disease [14, 15] that can be accelerated by microbial infection in its early phase [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…D) [4]. During the past decade, due to the antibacterial activity of housefly larvae and its products, they have been used mainly in preservation [11], environmental protection [12], and inhibition of multiresistant bacteria [13]. In recent years, several reports suggested that atherosclerosis is a chronic inflammatory disease [14, 15] that can be accelerated by microbial infection in its early phase [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from varied climatic settings and manure characteristics, different production techniques and process intensities have been tested. The research findings provide a detailed description on optimal production conditions and process organisation, comprising particulars, such as optimal larval stocking densities, husbandry of adults and egg harvesting techniques (Čičková et al, 2012a,b, 2013Pastor et al, 2011Pastor et al, , 2014.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…The housefly (Musca domestica) can yield animal protein in the biodegradation of organic waste [4], such as pig manure [5][6][7][8][9][10], cattle manure [11], poultry litter [12], and food waste [13]. The larvae obtained from these systems are alternative feed ingredients that are rich in nutrients from within the human food chain without the need to harvest part of the wild marine ecosystem.…”
Section: Introductionmentioning
confidence: 99%